Faktor-Faktor yang Mempengaruhi Presentase Gizi Kurang Balita 0-59 Bulan Tahun 2023 Menggunakan Spatial Autoregressive Model (Jurnal EurekaMatika, 2025)
Malnutrition within the population of children aged 0–59 months continues to be a major public health issue in Indonesia. This study aims to identify the factors influencing the percentage of undernourished children based on 2023 provincial-level data, taking into account spatial relationships between regions. The method used is the Spatial Autoregressive (SAR) model, which is capable of capturing spatial patterns in the data. The outcome variable is the proportion of undernourished children aged 0–59 months, whereas the explanatory variables include the proportion of children with low weight and vitamin A coverage, access to improved drinking water, and implementation of the Community-Based Total Sanitation (STBM) program. Moran’s I test indicates the presence of spatial dependence in the dependent variable, and the Lagrange Multiplier test suggests that the SAR model is more appropriate than the standard linear regression model. The analysis results show that low body weight and STBM significantly affect the prevalence of malnutrition. The SAR model also reveals that geographically adjacent regions tend to have similar rates of child malnutrition. A lower Akaike Information Criterion (AIC) value confirms that the SAR model is the most suitable approach for this study.Keywords: Children, Spatial autoregressive, Undernutrition.AbstrakKekurangan gizi pada balita usia 0–59 bulan masih menjadi isu penting dalam kesehatan masyarakat di Indonesia. Studi ini bertujuan mengidentifikasi faktor-faktor yang memengaruhi persentase Anak usia dini dengan masalah gizi berdasarkan data provinsi tahun 2023, dengan mempertimbangkan keterkaitan spasial antarwilayah. Metode yang digunakan adalah Spatial Autoregressive (SAR), yang mampu menangkap pola spasial dalam data. Variabel terikat adalah persentase balita gizi kurang, sementara variabel independen meliputi persentase balita dengan berat badan rendah, cakupan vitamin A, akses air minum layak, dan penerapan program Sanitasi Total Berbasis Masyarakat (STBM). Uji Moran’s I menunjukkan adanya keterkaitan spasial pada variabel dependen, dan hasil Lagrange Multiplier menunjukkan bahwa model SAR lebih sesuai dibanding regresi linear biasa. Berdasarkan hasil analisis, variabel berat badan rendah dan STBM berpengaruh signifikan terhadap tingkat gizi kurang. Model SAR juga menunjukkan bahwa wilayah yang berdekatan secara geografis cenderung memiliki tingkat gizi kurang yang serupa. Nilai AIC yang lebih rendah menguatkan bahwa SAR merupakan model terbaik dalam studi ini.
Keywords: Balita; Gizi kurang; Spatial autoregressive